Democratic Citizenship – A Conditioned Apprenticeship. A Call for Destabilisation of Democracy in Education - Olson, Maria (JSSE - Journal of Social Science Education, 2009)
We live in times when the search for a citizenship education that can transcend national, ethnical and cultural borders is an important part of educational policy. In times of increased pressure by the European Union on its nation states to provide for nation-transcending democracy, this question becomes crucial for national policymaking in Europe. In this text, Swedish education policy will be taken as a case in point in order to shed light on how this question is being handled in this particular national policy setting. It is argued that the policy’s citizen fostering agenda tends to be counterproductive in the sense that it is still situated in national notions of the relationship between democracy and education, which tend to exclude certain individuals and groups of people on an age-related and (ethno) cultural basis. It is further argued that these excluding features can be related to educational ideas about socialisation. The aim of this text is underlined by suggesting a different way of framing democracy and democratic citizenship education: to increase the potential of education as regards the renewal of democracy and democratic citizenship.